Magris Likes it Bad? Reflections on Ethics in a European Perspective. Issue 7 (17th November 2022) - Rebora, Simone
ABSTRACT: This essay examines Claudio Magris's literary production from the point of view of European normative ethics by drawing on recently-proposed theories of negative empathy and the hybrid hero. A brief overview of Magris's narratives and characters—from Illazioni su una sciabola (1985) ( Inferences from a Sabre, 1991) to Croce del Sud ) [Southern cross] (2020)—shows his peculiar interpretation of such theories and how he repurposes them for ethical goals. This is followed by a close reading of Un altro mare (1991) ( A Different Sea, 2017) which presents in detail the narrative and stylistic devices adopted by the author to establish an emotional connection with readers that can stimulate empathic identification together with critical thinking. Finally, the essay demonstrates the central role of Magris's work in a European ethical framework with the support of empirical evidence in the study of reading experience, combined with theoretical claims of several modern philosophers and literary scholars, including, among others, Martha Nussbaum, Stefano Ercolino, Massimo Salgaro, and Benjamin van Tourhout.